The contents of the news as seen by the public (D field study) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon Muhammad and his good and pure family.Public exposure to media news, especially radio and television, is of particular importance.Not only because of the importance of this function for both parties, the audience and the means, but also because the news works onFinding assumptions that are accepted - to some extent - by the public, which often lacks a confirmation mechanism.A natural facilitator, first and second, creating an unlimited relationship between the mediathe audience, the content of the news (the event’s cause), its characters, its source, and later its possible development)The three elements that were mentioned are (the subject of our research, because we do not study here the public preferencefor news), but how does the public see and care about the contents of the news? And it's an early subjectAccording to the modest researcher's studies.